Mindfulness and design: creating spaces for well being - Porter, Nicole; Bramham, Johanna; Thomas, Martin (Universidad de Sevilla, Vicerrectorado de Investigación, 2017)
What is the relationship between mindfulness therapy and the physical settings in which it is practiced? Mindfulness is defined as ―paying attention to what‘s happening in the present moment in the mind, body and external environment, with an attitude of curiosity and kindness‖ (MAPG, 2015: 5), however the qualities of the ‘external environment’ are rarely discussed in relation to mindfulness. As mindfulness based therapies increasingly applied in clinical and educational settings, this presents opportunities to explore how the design of a space – from the arrangement of furniture through to the qualities of a room, building, landscape, or wider spatial context – may influence mindfulness practice and its therapeutic benefits. In this workshop, a combination of research presentation and therapeutic practice was conducted. Literature from landscape architecture and architecture was presented, evidencing the effects of built environment design on mental health and well-being and emphasizing notions of ‘biophilic design’. Delegates were then invited to participate in guided mindfulness mediations, followed by facilitated group enquiry about the combined effects of formal mindfulness practice and the qualities of the physical space we were practicing within.